2012
DOI: 10.1099/jmm.0.040113-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of infective endocarditis: comparison of the LightCycler SeptiFast real-time PCR with blood culture

Abstract: JMM CorrespondenceDiagnosis of infective endocarditis: comparison of the LightCycler SeptiFast real-time PCR with blood culture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Interestingly, all samples were from patients with bacterial endocarditis. This finding is in line with the notion that PCT does not increase significantly in patients with bacterial endocarditis, reaching median values of 0.21 ng/ml [30], and outlines the fact that SF can be successfully used for diagnosis of endocarditis [31].…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, all samples were from patients with bacterial endocarditis. This finding is in line with the notion that PCT does not increase significantly in patients with bacterial endocarditis, reaching median values of 0.21 ng/ml [30], and outlines the fact that SF can be successfully used for diagnosis of endocarditis [31].…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, Mencacci et al. suggest that SF may be a useful tool for the detection of endocarditis pathogens in patients undergoing antimicrobial therapy [41]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study of 51 febrile intravenous drug users (IDUs), SepsiTest® was found to have 87% sensitivity and specificity for detecting microorganisms compared to blood culture, but showed perfect diagnostic performance in detecting pathogens in patients with infective endocarditis (66). In another similar study, SeptiFast® was found to be useful in the diagnosis of infective endocarditis, particularly in patients who had been pre-treated with antibiotics (67). …”
Section: Multiplex Technologies For Direct Diagnosis From Clinicalmentioning
confidence: 99%
“…Multiplex technologies have also been used in other types of microbial infections including bone and joint infections (64) and infectious endocarditis (6567). In infectious endocarditis, patients can have negative blood culture results due to low pathogenic load in the blood, prior antimicrobial therapy, or the presence of fastidious microorganisms.…”
Section: Multiplex Technologies For Direct Diagnosis From Clinicalmentioning
confidence: 99%